2006
DOI: 10.1369/jhc.5a6738.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Bone Morphogenetic Protein-signaling Smads during Long-bone Distraction Osteogenesis

Abstract: In this study we investigated the expression of bone morphogenetic protein (BMP)-signaling Smads in distraction osteogenesis (DO). Osteotomy of the right tibia was performed in 14 skeletally mature white New Zealand male rabbits. Lengthening was started 1 week later at a rate of 0.5 mm/12 hr and was maintained for 3 weeks. Expression of Smad proteins 1, 4, 5, 6, 7, and 8 and Smad ubiquitin regulatory factors (Smurfs) 1 and 2 was evaluated in the distracted zone using immunohistochemistry. Expression of recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…We and others (Ai-Aql et al, 2008;Haque et al, 2007;Haque et al, 2008;Haque et al, 2006;Rauch et al, 2000) have shown that the mechanical forces applied during DO lead to the temporal and spatial expression of numerous cytokines, growth factors including BMP (Bone Morphogenetic Proteins), FGF (Fibroblast Growth Factor), IGF (Insulin Growth Factor), TGFB (Transforming Growth Factor B), PDGF (Platelet Derived Growth Factor), vascular factors VEGF (Vascular Endothelial Growth Factor), HIF (Hypoxia Induced Factor), as well as extracellular matrix proteins (Sato et al, 1998) and matrix metalloproteinases (Marucci et al, 2002). During the distraction phase, while the distraction forces are still being applied, many of these molecules are up-regulated and then, once the distraction forces cease at the end of the distraction phase, they become down-regulated.…”
Section: Molecular Events and Mechanism Of Bone Formation In Distractmentioning
confidence: 60%
See 1 more Smart Citation
“…We and others (Ai-Aql et al, 2008;Haque et al, 2007;Haque et al, 2008;Haque et al, 2006;Rauch et al, 2000) have shown that the mechanical forces applied during DO lead to the temporal and spatial expression of numerous cytokines, growth factors including BMP (Bone Morphogenetic Proteins), FGF (Fibroblast Growth Factor), IGF (Insulin Growth Factor), TGFB (Transforming Growth Factor B), PDGF (Platelet Derived Growth Factor), vascular factors VEGF (Vascular Endothelial Growth Factor), HIF (Hypoxia Induced Factor), as well as extracellular matrix proteins (Sato et al, 1998) and matrix metalloproteinases (Marucci et al, 2002). During the distraction phase, while the distraction forces are still being applied, many of these molecules are up-regulated and then, once the distraction forces cease at the end of the distraction phase, they become down-regulated.…”
Section: Molecular Events and Mechanism Of Bone Formation In Distractmentioning
confidence: 60%
“…First, the expression of various members of the BMP signaling pathway was extensively analyzed, at the protein level using www.intechopen.com Distraction Osteogenesis and Its Challenges in Bone Regeneration 197 immunohistochemistry and at the mRNA level using RT-PCR, and it was shown by us (Haque et al, 2007;Haque et al, 2008;Haque et al, 2006;Rauch et al, 2000) and others (AiAql et al, 2008) that BMP ligands, receptors, transcription factors and downstream targets are up-regulated during the distraction phase and then down-regulated once the mechanical forces of distraction cease. Fig.…”
Section: Importance Of Bmps In Distraction Osteogenesismentioning
confidence: 99%
“…They were then incubated in 10% normal horse serum (NHS) for 20 minutes at 37°C. The NHS and all subsequent reagents were diluted in PBS containing 0.1% bovine serum albumin, 200 μL of the diluted solution was added to each slide and incubated in a moisture chamber (22). The NHS was removed, and the slides were incubated at 37°C with monoclonal anti α-actin smooth muscle specific antibody (Cat.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Score 0 was given if there was no staining, score 1 for weak intensity staining followed by score 2 with mild intensity staining and final score 3 with the highest intensity of the staining of the granules. The scoring was done using double-blinded method (Haque et al 2006). …”
Section: Expression Of 11β-hsd1 Enzyme In Livermentioning
confidence: 99%